2009
DOI: 10.1007/s11094-010-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

A rapid chromatographic/mass spectrometric method for digoxin quantification in human plasma

Abstract: The relatively simple liquid-liquid extraction LC-MS/MS method using a UPLC column for measurement of digoxin concentrations both in medium and human plasma is described. Digitoxin was used as internal standard. The developed method possesses satisfactory accuracy, precision, and repeatability, and is economical and not time-consuming. It is the first method for precise measurement of digoxin concentrations in human plasma using combined HPLC equipment and UPLC column with a low limit of quantitation equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Additionally, the method was also directed at semi-quantitative analysis of deslanoside and lanatoside. Several individual liquid chromatography-mass spectrometry (LC-MS) assays for digoxin and digitoxin [20][21][22][23][24][25][26][27][28][29][30] have been reported as well as in combination with their metabolites or related cardiac glycosides. [19,[31][32][33][34][35] To our knowledge, no LC-MS/MS method has been described for simultaneous quantification of the above combination of drugs and their metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the method was also directed at semi-quantitative analysis of deslanoside and lanatoside. Several individual liquid chromatography-mass spectrometry (LC-MS) assays for digoxin and digitoxin [20][21][22][23][24][25][26][27][28][29][30] have been reported as well as in combination with their metabolites or related cardiac glycosides. [19,[31][32][33][34][35] To our knowledge, no LC-MS/MS method has been described for simultaneous quantification of the above combination of drugs and their metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The generated ions of digoxin include the positive ions 8,11,13,15 [M + Li] +9 and the negative ions [M-H] À , [M + HCOO] -, 14 [M + CF 3 COO] -. 6 However, the full MS-SIM indicated that the presence of the formic acid gave rise to formate-adduct ions [M + HCOO] À as the predominant ion for digoxin, with an m/z value of 825.42781. The formation of the formate-adduct ions resulted in a very simple mass spectra for digoxin.…”
Section: Hrms Parameter Optimizationmentioning
confidence: 99%
“…In the past decade, determination of digoxin in biological specimens was primarily accomplished using liquid chromatography tandem mass spectrometry (LC-MS, LC-MS/MS) 4,[6][7][8][9][10][11][12][13][14][15] and surfaceassisted laser desorption/ionization mass spectrometric detection (SALDI/MS). 16 MS/MS offered considerable advantages, including speed, selectivity, sensitivity, and robustness, and was a highly efficient analytical tool for biological specimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of analytical, mostly single-analyte, methods for quantification of CGs in biological matrices have been described [11,[17][18][19][20][21][22][23][24]. As a detection technique, these methods utilized mass spectrometry (MS) coupled to liquid chromatography (LC), which, thanks to its good selectivity and sensitivity, has nowadays become the method of choice for many applications including toxin analysis.…”
Section: Introductionmentioning
confidence: 99%